On the role of information in educational choice (Doctoral dissertation) - FACCHINELLO, Luca (Institutional Knowledge at Singapore Management University, 2016)
When students are uncertain about own ability, information might affect their academic choices. The thesis consists of three self-contained chapters that explore different facets of this theme. The first chapter studies theoretically and empirically the role of early grade assignment in education choice, focusing in particular on mechanisms. The main argument is that early grading affects differently the choices of students with different academic ability and socioeconomic status. The second chapter investigates empirically whether repeatedly surveying compulsory school students affects their educational choices, attainment, and long-run labor market outcomes. The basic idea is that educational surveys might contain information relevant for the choices of the students. The last chapter studies empirically whether, and how, students’ choices in compulsory school are affected by peer ability. If students assess their academic ability in relation to their classmates, peer ability might have an effect on their academic choices. A short summary of each chapter follows.